Research of methods for evaluating the effectiveness of public relations activities - A. A. Sazonov (Вестник университета)
The article is devoted to the study of the main methods of evaluating the effectiveness of activities in the field of public relations. The paper indicates the main features that characterize modern PR technologies: innovation, manufacturability, consistency, the guarantee of certain practical results, and so on. Public relations are currently one of the fastest-growing components of the marketing communications complex, which is aimed at forming and strengthening a positive image of the company in the eyes of public groups. The study ascertains that to calculate the effect of PR campaigns and return on investment (ROI), it is necessary to use the construction of special multicomponent correlation models, where media analytical indicators can be correlated with certain financial results. The author considers the metric of the use value norm used to assess the current level and effectiveness of the company’s communication policy, taking into account the complex of various PR activities. The study gives an algorithm for finding an effective commercial offer in the B2B segment. The paper creates a formula that allows calculating the socio-economic efficiency of a PR company. In conclusion of the article, the author presents groups of indicators that should be paid attention to by the company’s top management to evaluate conducted PR campaign.